Enhanced refocusing of fat signals using optimized multipulse echo sequences. Issue 4 (24th May 2012) - Stokes, Ashley M.; Feng, Yesu; Mitropoulos, Tanya; Warren, Warren S.
<x xml:space="preserve">Abstract</x> Endogenous magnetic resonance contrast based on the localized composition of fat in vivo can provide functional information. We found that the unequal pulse timings of the Uhrig's dynamical decoupling multipulse echo sequences significantly alter the signal intensity compared to conventional, equal‐spaced Carr–Purcell–Meiboom–Gill sequences. The signal increases and decreases depending on the tissue and sequence parameters, as well as on the interpulse spacings; particularly strong differences were observed in fatty tissues, which have a highly structured morphology and a wide range of chemical shifts and J‐couplings. We found that the predominant mechanism for fat refocusing under multipulse echo sequences is the chemical structure, with stimulated echoes playing a pivotal role. As a result, specialized pulse sequences can be designed to optimize refocusing of the fat chemical shifts and J‐couplings, where the degree of refocusing can be tailored to specific types of fats. To determine the optimal time delays, we simulated various Uhrig dynamical decoupling and Carr–Purcell–Meiboom–Gill pulse sequence timings, and these results are compared to experimental results obtained on excised and in vivo fatty tissue. Applications to intermolecular multiple quantum coherence imaging, where the improved echo refocusing translates directly into signal enhancements, are presented as well. Magn Reson Med 69:1044–1055, 2013. © 2012 Wiley Periodicals, Inc.